The association between serum growth differentiation factor 15 and insulin resistance in women diagnosed with polycystic ovary syndrome - Yufeng Mei; Wanzhen Li; Zhenni Chen; Min Wang (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is strongly associated with metabolic abnormalities, with 50–70% of patients exhibiting insulin resistance (IR), which significantly impacts the reproductive health of women in their reproductive years. Growth differentiation factor 15 (GDF15), a hormone responsive to nutritional stress, has been implicated in several diseases. This study sought to clarify the relationship between GDF15 levels and IR condition in PCOS patients. Based on the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), patients were categorized into an IR-PCOS group (n = 124) and a non-insulin-resistant group (non-IR-PCOS group, n = 109). Fasting blood samples were collected to measure GDF15 concentrations. To assess metabolic complications in relation to GDF15 levels, patients were also classified into high and normal GDF15 groups. Serum GDF15 levels were significantly higher in IR-PCOS patients (median 772.94 pg/ml) compared to non-IR-PCOS patients (median 575.80 pg/ml, P < 0.05). The high GDF15 group showed more severe metabolic and lipid abnormalities than the normal GDF15 group. Spearman correlation analysis revealed a correlation between increased GDF15 levels and impaired glucose metabolism. Logistic regression analysis identified GDF15, HDL-C, and prolactin as risk factors for IR in PCOS, and the fully adjusted regression coefficient for GDF15 levels and IR prevalence was 4.490 (95% CI 1.541 to 13.088). Restricted cubic spline analysis confirmed a positive association between GDF15 levels and IR within a specific range. The combined predictive probability of GDF15, prolactin, and HDL-C for IR was 0.763 (95% CI 0.701 to 0.826) according to ROC analysis. Elevated GDF15 levels may be associated with IR in PCOS patients, suggesting a potential role for GDF15 in the pathophysiology of IR in this condition.